INNOVATIVE METHODOLOGY OF INCREASING PHYSICAL ACTIVITY IN YOUTH BASED ON THE “WORKOUT 3+3” PROGRAM (Universal International Scientific Journal, 2026)
: This article discusses the theoretical foundations and practical significance of the innovative program “Workout 3+3” aimed at increasing the physical activity of young people. In modern conditions, the development of effective training programs is urgent, since a decrease in physical activity negatively affects health and work capacity. The “Workout 3+3” program serves to gradually develop the physical fitness of young people. The program consists of three stages: at the first stage, adaptation and basic skills are formed; at the second stage, the complexity of the exercises is increased, strength, speed and endurance are developed; at the third stage, maximum physical capabilities are improved through high-level exercises
Keywords: : exercise, physical activity, youth, innovative training program, physical fitness, strength, speed, endurance